Anionic polyelectrolytes in titanosilicate molecular sieve synthesis towards simultaneously accomplishing low production cost and high catalytic activity. Issue 38 (13th June 2018) - Fu, Kairui; Wang, Jingui; Wang, Yichen; Shao, Yuanchao; Zhu, Jiaqi; Li, Tianduo
Abstract : Anionic polyelectrolytes can help to directly achieve low-cost, titanium-rich, diffusion restriction-free and 100%-yield titanium silicalite-1. Abstract : Assisted by an anionic polyelectrolyte of poly(acrylic acid) (PAA), high-performance titanium silicalite-1 (TS-1) could be facilely synthesized at very low usage of expensive organic templates (tetrapropylammonium hydroxide). The presence of PAA helped to incorporate more active Ti species into the TS-1 framework and change the morphology to a plate-like shape, which was beneficial to molecular diffusion among its micropores to access the Ti active sites. Therefore, TS-1 synthesized with PAA showed much higher catalytic activity than that synthesized using the traditional synthesis without polyelectrolytes, and only a 30% usage amount of organic template was used. Moreover, this ultra-cheap catalyst also displayed a better catalytic activity than commercial TS-1 synthesized via a series of complicated preparation processes including alkene epoxidation with hydrogen peroxide as a green oxidant.